Prognostic value of circulating microRNA-21-5p and microRNA-126 in patients with acute myocardial infarction and infarct-related artery total occlusion - Mi, Xiao-long; Gao, Yu-ping; Hao, Da-jie; Zhang, Zhi-jun; Xu, Zheng; Li, Tong; Li, Xue-wen (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiovascular disease, including acute myocardial infarction (AMI), is a major global cause of mortality and morbidity. Specificity and sensitivity limit the utility of classic diagnostic biomarkers for AMI. Therefore, it is critical to identify novel biomarkers for its accurate diagnosis. Cumulative studies have demonstrated that circulating microRNAs (miRs) participate in the pathophysiological processes of AMI and are promising diagnostic biomarkers for the condition. This study aimed to ascertain the diagnostic accuracy of circulating miR-21-5p and miR-126 used as biomarkers in patients with AMI and infarct-related artery total occlusion (IR-ATO) or infarct-related blood-vessel recanalization (IR-BVR). Methods: The expression of miR-21-5p and miR-126 was examined separately in 50 healthy subjects, 51 patients with IR-ATO AMI, and 49 patients with IR-BVR AMI using quantitative real-time polymerase chain reaction. Results: When compared with the control group, the IR-ATO AMI group exhibited increased miR-21-5p (p < 0.0001) and miR-126 (p < 0.0001), and the IR-BVR AMI group exhibited increased miR-21-5p (p < 0.0001). However, there was no significant difference in miR-126 between the IR-BVR AMI and the control groups. Spearman’s correlation coefficient showed a strong correlation between miR-21-5p, miR-126, cardiac troponin-I, and creatine kinase isoenzyme in all three groups, while a receiver operating characteristic analysis revealed that miR-21-5p and miR-126 exhibited considerable diagnostic accuracy for IR-ATO AMI. Conclusion: Circulating miR-21-5p and miR-126 may be promising prognostic biomarkers for patients with AMI and IR-ATO.